(untitled) (Research, Society and Development, 2022)
The biological properties of plants have always aroused curiosity in the scientific community because, since ancient times, man has used phytotherapy to prevent and cure diseases. Currently, many studies prove the pharmacological effects of vegetables and medicinal applications ranging from pain relief, control of inflammation and infections, antioxidant action to antitumor action. In dentistry, the use of phytotherapy has grown and research into the use of plant derivatives on periodontal and endodontic infections, caries, and oral candidiasis, for example, is expanding. The objective of the present review was to diagnose the current panorama of research on herbal medicine in dentistry based on scientific evidence present in the literature. Works available in the PUBMED, BVS, Google academic, and Scielo databases were used. In the present review, it was found that many in vitro, in vivo, and clinical trials are being carried out to prove the efficacy and safety of plant compounds and in dentistry, it is observed that the study and use of phytotherapy are increasingly broad. Among the main therapeutic applications of plants in dentistry, we can mention the analgesic, anti-inflammatory, antimicrobial (including antibacterial and antifungal action), and anxiolytic activity, and the main phytotherapeutics frequently used are: Malva sylvestris, Camellia sinensis, propolis, Carica papaya, Glycyrrhiza glabra, Valeriana officinalis, and Passiflora incarnata. Thus, it can be concluded that the benefits of phytotherapy in dentistry are numerous and the continuity of research is essential for plant products to reach dental clinics in all regions of Brazil.